Actividad antioxidante y contenido de fenoles totales de la hoja y látex de Brosimum alicastrum Sw. (MORACEAE) procedente del Distrito de Sacanche, San Martín – 2022 - Portalanza Rojas, Siria Rosina (2024)
Antioxidants are of utmost importance because they act by neutralizing free radicals, thus preventing them from causing damage to cells, thus preventing degenerative diseases. This study focused on the comparison of the antioxidant activity and total phenolics of the leaves and latex of Brosimum alicastrum tres, species considered to have many medicinal benefits, from the district of Sacanche, San Martín. Antioxidant activity was determined through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis (3ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods. Meanwhile, the total phenolic content was quantified with the Folin-Ciocalteu method. The leaves showed greater antioxidant activity than latex with both methods (p<0.01): DPPH (220.20 ± 0.58 and 8.97 ± 0.05 µmol trolox/g, respectively) and ABTS (219.91 ± 0.39 and 72.67 ± 0.53 µmol trolox/g, respectively). The concentration of total phenols was also higher in the leaves than in the latex of B. alicastrum: 568.92 ± 0.11 and 348.17 ± 0.15 mg gallic acid/g, respectively (p<0.01). There was a positive correlation between antioxidant activity and total phenolic content of B. alicastrum. The antioxidant potential of B. alicastrum leaves was confirmed and the need to carry out more detailed studies for its application in the treatment of degenerative diseases.